Anisakis simplex Hernández-Orts, Viola, García, Crespo, González, García-Varela & Kuchta, 2015, s.l. - Hernández-Orts, Jesús S.; Viola, M. Natalia Paso; García, Néstor A.; Crespo, Enrique A.; González, Raúl; García-Varela, Martín; Kuchta, Roman (Zenodo, 2015)
Anisakis simplex s.l. (Rudolphi, 1809) Host: Balaenoptera borealis Lesson Site in host: stomach Locality: San Antonio Oeste, Río Negro province References: Leonardi et al . (2011) Host: Cephalorhynchus commersonii (Lacépède) Site in host: stomach Locality: Bahía Grande, Santa Cruz province Specimens in collections: BMNH (accession numbers not available)V References: Gibson and Harris (1979) Published as part of Hernández-Orts, Jesús S., Viola, M. Natalia Paso, García, Néstor A., Crespo, Enrique A., González, Raúl, García-Varela, Martín & Kuchta, Roman, 2015, A checklist of the helminth parasites of marine mammals from Argentina, pp. 301-334 in Zootaxa 3936 (3) on page 318, DOI:10.11646/zootaxa.3936.3.1, http://zenodo.org/record/236696